Hope over fate : Fazle Hasan Abed and the science of ending global poverty - MacMillan, Scott, 1974- (Dhaka : Baatighar ; Lanham : Rowman & Littlefield, 2022)
"This book tells the story of Fazle Hasan Abed (1936-2019), a former finance executive with almost no experience in relief aid who founded BRAC in 1972. Abed's methods have changed the way global policymakers think about poverty"--
Includes bibliographical references and index.
AAL, GenEd
Keywords: Abed, F. H; Bangladesh Rural Advancement Committee; Social service, Rural -- Bangladesh; Poverty; Economic development; Economics